Acute HIV Infection in Pregnancy: The Case for Third Trimester Rescreening - Jocelyn Wertz; Jason Cesario; Jennifer Sackrison; Sean Kim; Chi Dola (Case Reports in Infectious Diseases)
Combination testing with anti-HIV Elisa and Western blot is both sensitive and specific for diagnosis of established HIV-1 infection but could not detect acute HIV infection (AHI). AHI is a time of extremely high viral load, which may correlate to increased risk of horizontal or vertical transmission. Thus, early identification of AHI could allow for interventions to decrease transmission. However, recognition of AHI can be challenging as symptoms could be absent or nonspecific, therefore, AHI is often not detected, particularly in pregnancy. We present a case report of AHI in a pregnant woman who presented with headache and fever. She tested negative for HIV in the first trimester and at time of AHI at 26 3/7 weeks by anti-HIV Elisa, but was diagnosed with AHI based on an HIV RNA viral load of 434,000 copies/mL. This report presents a case for improved awareness of AHI in pregnancy, and the need for repeat HIV testing in late pregnancy, and highlighted that early detection of AHI might be possible with adding HIV RNA testing at time of standard anti-HIV Elisa screening test in pregnancy. Novel laboratory approaches including pooling of sera for HIV RNA could reduce the cost of HIV RNA testing.